2012
DOI: 10.3329/bjmm.v4i2.10822
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Antibody to Hepatitis G Virus Among the Risk Groups and Healthy Population of Bangladesh

Abstract: Dr Mahmuda Siddiqua E-mail : mahmuda99@yahoo.com hepatitis, occurring in patients with no other known etiology. 5It is well established that HGV maintains a high and stable level of plasma viremia for many years, 6 which indicates it's efficient and active replication. Before the establishment of antibody detection methods, prevalence rates of HGV RNA in general population varied between less than 1 to 4% in different countries.7 With the development of new tests for detection of anti-HGV antibodies about 3 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…Among the study population in the current study 3 (1.7%) respondents were seropositive for HGV and rest 177 (98.3%) respondents were seronegative for HGV infection. In this regards Siddiqua et al 22 reported the overall prevalence of HGV antibody was 3.2% in a study conducted in Bangabadhu Sheikh Mujib Medical University, Dhaka, which was little high from the present study and may be due to inclusion of commercial sex workers in their study.…”
Section: Resultscontrasting
confidence: 59%
See 2 more Smart Citations
“…Among the study population in the current study 3 (1.7%) respondents were seropositive for HGV and rest 177 (98.3%) respondents were seronegative for HGV infection. In this regards Siddiqua et al 22 reported the overall prevalence of HGV antibody was 3.2% in a study conducted in Bangabadhu Sheikh Mujib Medical University, Dhaka, which was little high from the present study and may be due to inclusion of commercial sex workers in their study.…”
Section: Resultscontrasting
confidence: 59%
“…Seropositivity did not differed between male and female (p=0.547). Siddiqua et al 22 found that there was no significant difference seen in their study about the prevalence of HGV between the male (3.2%) and female (3.1%).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation